(untitled) (Psicologia USP, 1996)
This paper reports the creation of the Laboratory of Popular Education and Health at the Psychology Department of University of Santa Catarina, Brazil. Ten years ago some teachers of this Department started to develop isolated actions in order to extend psychological services to lower class people, traditionally excluded from this kind of professional care. In the course of this work the inefficacy of theoretical and methodological framework of traditional Clinical Psychology became evident. They summed up their experiences in the Laboratory, where two urgent tasks were in need: the search for new psychogical theories and practices and the reexamination of graduate courses of Psychology, in order to cope with the Brazilian social problems.